Interpreting Article 17 TFEU: New Openings towards a European Law and Religion System (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Introduction: From the Traditional Interpretation towards New Openings - 2. Some interpretative difficulties - 3. The Necessary Balance with Other European Interests - 4. Conclusions.Interpreting Article 17 TFEU: New Openings towards a European Law and Religion SystemABSTRACT: Article 17 TFEU has been mainly interpreted as a “safeguard clause” aimed at preventing the EU from affecting (even indirectly) national disciplines religiously connoted. Although this traditional interpretation seems to find confirmation in the letter of the provision, in the systematic reading with Article 4 TEU, second paragraph, as well as in the original will of the parties, some scholars started giving credit to a different interpretation: the Article could allow the development of a European Law and Religion System. This article aims to investigate the current possibility for the aforementioned change of prospective. It focuses on three key factors: the interpretative difficulties concerning the Article, the recent jurisprudential evolution of the Court of Justice of the European Union and the growing axiological-systematic relevance of the Charter of Fundamental Rights of the European Union. This work argues that Article 17 TFEU does not recognize a national competence ex ante in all religious matters; it only requires the EU to refrain from regulating cases that are concretely characterized by a high rate of denominational specificity.